Pharmacokinetics and Pharmacodynamics of Canakinumab in Patients With Systemic Juvenile Idiopathic Arthritis. (8th June 2016) - Sun, Haiying; Van, Linh M.; Floch, David; Jiang, Xuemin; Klein, Ulf R.; Abrams, Ken; Sunkara, Gangadhar
Abstract: The characterization of the pharmacokinetic (PK) and pharmacodynamic (PD) properties in pediatric patients is essential in supporting the recommended dosage of canakinumab in the relevant population. Here the PK and PD properties of canakinumab—a monoclonal antibody—in pediatric patients with systemic juvenile idiopathic arthritis (SJIA) are presented. Blood samples were obtained from 4 phase 2/3 clinical studies in patients with SJIA. Canakinumab PK properties and total interleukin (IL)‐1β kinetic properties were characterized by a population‐based PK‐binding model. On administration, canakinumab increased total IL‐1β complex in SJIA patients. Canakinumab clearance and volume of distribution were not impacted by age in pediatric patients after correction for the patient's body weight. The estimated serum clearance of canakinumab was 0.106 ± 0.00689 L/day, with a corresponding volume of distribution at steady state of 3.2 L and an estimated half‐life of 22 days, based on a model typical body weight of 33 kg. Body‐weight–based dosing provided comparable canakinumab exposure across the age groups in patients 2 to <20 years with SJIA. In younger children, a modest increase in the turnover rate of IL‐1β was observed. Compared to other indications, IL‐1β production rate was higher and clearance was slower in patients with SJIA. Low immunogenicity incidence of 3.1% was observed, and none of the patients had neutralizing antibodies. In conclusion, the PK/PD findings further support dose selection of canakinumab in patients with SJIA.